FRI0608 Diagnostic Value of the Prednisolone Test in Patients with Possible Rheumatoid Arthritis. (9th June 2015) - Kiltz, U.; von Zabern, C.; Baraliakos, X.; Heldmann, F.; Mintrop, B.; Andreica, I.; Sarholz, M.; van Werde, M.; Klink, C.; Krause, D.; Dybowski, F.; Kalthoff, L.; et al.
Abstract : Background: In patients with tender and swollen finger joints, the differential diagnosis between rheumatoid arthritis (RA) and osteoarthritis (OA) of the hands can be initially difficult. In a previous pilot study we have shown that the positive response to a 3-day-course of 20 mg prednisolone (the "pred-test") differentiates between RA and OA of the hands. An subjective percentage of improvement of 40% was found to discriminate best. Objectives: To study the diagnostic value of the pred-test in patients with possible RA. Methods: Consecutive patients with hand pain referred because of suspected RA (n=100) were included in the study. Clinical examination by one experienced rheumatologist, laboratory tests, and magnetic resonance imaging (MRI) were regularly performed. All patients received 1g paracetamol/day for 5 days. On days 3-5 a morning dose of 20 mg of prednisolone was added. Hand pain was quantified on a numerical rating scale (NRS 0–10) and the subjective percentage of improvement recorded. The predefined cut-off of 40% improvement was applied to differentiate between responders and non-responders. Diagnoses were made by the expert who was unaware of the treatment result. Patients were reexamined at week 12 to confirm the diagnosis. Results: There were 95 patients with complete data (Tab.1 ). RA was diagnosed in about half of the patients. RA patients had more swollen joints, higher CRP levels and a comparable HAQ (Tab.1 ). The pred test was positive in 42.1% of the patients (40/95). The median percentage of improvement after 3 days of 20 mg of prednisolone was higher in RA than in OA: 50% (IQR 30%>60%) vs. 20% (IQR 10%>30%), p<0.001. The sensitivity and specificity of the pred-test was 65.9% (31/47) and 81.2% (39/48), and the positive and negative predictive value was 0.77 and 0.70, respectively. Conclusions: This is the first evaluation of the widely used pred-test that has ever been performed. We found that this test has a moderate sensitivity and good specificity. We propose that rheumatologists use this test in uncertain clinical situations to be able to better differentiate between inflammatory arthritis and osteoarthritis. Finally, we hope that a negative test result will prevent patients to receive unnecessary glucocorticoid treatment, while a positive test will help to identify patients with inflammatory arthritis who can then receive proper treatment. Disclosure of Interest: None declared